Reforming Land and Real Estate Markets - Galal, Ahmed; Razzaz, Omar (World Bank, Washington, DC, 2014)
Land and real estate reforms have not been effective at achieving their objectives, in part because of how they have been designed and implemented. To be successful, reforms must become comprehensive in design, argue the authors, although implementation may be phased over time and take local conditions into account. Reform must include three elements: 1) Institutional reforms that better define property rights, reduce information asymmetry, and improve contract enforcement. 2) Capital market reforms that make mortgage finance available at reasonable rates, especially for the poor. 3) Market reforms that reduce or eliminate the main distortions in the prices of goods and services produced by land and real estate assets. In their review of land and real estate reforms supported by the World Bank, the authors find that such reforms receive less attention at the conceptual stage than they should, considering their great impact on poverty, growth, and stability. They base their conclusion on the limited coverage of land and real estate issues in country assistance strategies, the main vehicle for identifying priority areas for reform. Most Bank-supported projects do not address all three elements critical for reform. And most provide no justification for excluding them, and no plan for follow-up. The Bank's Operations Evaluation Department rates Bank-supported land and real estate projects relatively well on outcome and sustainability but not on institutional development. But land and real estate reform is institutional by nature. The authors urge the Bank and policymakers to change course. After a comprehensive assessment of the status of real estate institutions and markets, all actors in this sector should be pulled together to develop a comprehensive approach to land and real estate reform.